Mediasi Sebagai Alternatif Non-Litigasi Dalam Penyelesaian Sengketa Pemutusan Hubungan Kerja: Kajian Terhadap Kepastian Hukum dan Keadilan - Baskoro, Ale Dani; Juliasari, Alya Puspita; Dharma, Dhiva Aurora Pramhesta (Media Hukum Indonesia (MHI), 2025)
This research aims to analyze the role of mediation as a non-litigation alternative in the settlement of employment termination disputes and to examine how far mediation can provide legal certainty and justice for the disputing parties. The study employs a normative juridical method with a statutory and case approach. Research instruments include document studies of legislation, Industrial Relations Court decisions, and relevant legal literature. Data analysis was conducted qualitatively, focusing on legal interpretation and the practical implementation of mediation in Indonesia's labor law system. The findings indicate that although mediation offers a fast and efficient solution, challenges such as non-compliance with agreements and limited understanding of the mediation process remain significant obstacles. Nevertheless, mediation remains relevant as a vital instrument for achieving restorative justice and reinforcing legal certainty in industrial relations.